Periodontitis in India and Bangladesh. Need for a population based approach in epidemiological surveys. A Literature review (Bangladesh Journal of Medical Science, 2010)
Background: Early surveys showed people of India and its neighbors to be highly susceptible to periodontitis. This was based on the early surveys which estimated a higher prevalence. Aim: This paper reviews the prevalence of periodontitis in India and Bangladesh and attempts to find out why the populations of the Indian subcontinent were considered more susceptible to periodontitis. Settings and design: Review of periodontitis prevalence studies on the Indian and Bangladeshi population. Methods and material: After identifying articles from Pub Med, DAOJ and hand searching, the epidemiology of periodontitis is reviewed. Results and conclusion: This review identifies that very few studies have been done on representative population. Yet it can be certainly concluded that there is a high prevalence of periodontitis in the adults and the economically weak population which can be reduced by adopting preventive public health strategies. Conclusions: Standardized population based studies in a representative population with a robust design to identify the true prevalence of periodontitis is needed. Keywords: Periodontitis; India; Bangladesh; epidemiology; prevalence. DOI: 10.3329/bjms.v9i3.6466Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.124-130